2015
DOI: 10.1002/dev.21313
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioned responses and PTSD symptoms in children: Sex differences in fear‐related symptoms

Abstract: Fear conditioning studies in adults have found that posttraumatic stress disorder (PTSD) is associated with heightened fear responses and impaired discrimination. The objective of the current study was to examine the association between PTSD symptoms and fear conditioned responses in children from a highly traumatized urban population. Children between 8 and 13 years old participated in a fear conditioning study in addition to providing information about their trauma history and PTSD symptoms. Results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 45 publications
(55 reference statements)
5
50
1
Order By: Relevance
“…In the secondary analyses, we included this measure as a covariate. We also included sex as a covariate given that we previously found significant sex differences in FPS (Gamwell et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the secondary analyses, we included this measure as a covariate. We also included sex as a covariate given that we previously found significant sex differences in FPS (Gamwell et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…The participants were recruited as part of an ongoing longitudinal study of trauma exposure in children. A subset of data from this study has been published previously (Jovanovic et al, 2014; Gamwell et al, 2015); however, the current study only included individuals that had (1) complete startle data, (2) available information about maternal presence during the startle testing, and (3) data on maternal warmth. In order to be eligible for the study, child participants had to be between 8 and 13 years of age and willing to participate; exclusion criteria were a diagnosis of autism spectrum disorders, bipolar or psychotic disorders, or cognitive disability.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, youth with PTSD did not exhibit a differential conditioned SCR when compared to youth without PTSD [83]. In contrast, another study found PTSD symptom severity to have a small-to-moderate association with larger SCRs to the CS+ [82]. Furthermore, youth from a high trauma-exposure population and with high anxiety were found to exhibit greater FPS to the CS+ and CS- during conditioning, compared to youth from the same population who had low anxiety [81].…”
Section: Threat Conditioning and Extinction In Youth With Ptsd Trmentioning
confidence: 99%
“…Furthermore, youth from a high trauma-exposure population and with high anxiety were found to exhibit greater FPS to the CS+ and CS- during conditioning, compared to youth from the same population who had low anxiety [81]. Gender [82] and age [81] were found to influence threat conditioning within trauma-exposed youth. Boys from a highly trauma-exposed population were found to exhibit greater differential conditioning, compared to girls [82], and younger children exhibited poorer discrimination between CS+ and CS-, compared to older youth [81].…”
Section: Threat Conditioning and Extinction In Youth With Ptsd Trmentioning
confidence: 99%
See 1 more Smart Citation